PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PADA PT. MEDIAINDO SEJAHTERA DI JAKARTA - Lucia Maduningtias (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2020)
This study aims to determine the effect of motivation and work discipline on employee productivity at PT. Mediaindo Sejahtera in Jakarta. The method used is explanatory research with analytical techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study have a significant effect on employee productivity by 46.7%, the hypothesis test obtained t count t table or (7.809 2.003). Work discipline has a significant effect on employee productivity of 36.0%, the hypothesis test is obtained t count t table or (5.608 2.003). Motivation and work discipline simultaneously have a significant effect on employee productivity by 55.9%, the hypothesis test is obtained F count F table or (34.847 2.770).